READING ALOUD ACTIVITIES OF ELEMENTARY SCHOOL STUDENTS THROUGH THE LETS READ APPLICATION - Sari, Dessy Dwitalia; Widya Rini, Tika Puspita; Susilawaty, Susilawaty (Universitas Muhammadiyah Mataram, 2022)
Abstrak: Kemampuan membaca merupakan keterampilan yang tidak bisa dihasilkan secara instan. Keterampilan membaca perlu dibiasakan dalam kehidupan sehari-hari siswa, terutama siswa kelas rendah yang masih berada pada tahap membaca permulaan. Adanya pandemi Covid-19 mempengaruhi kebiasaan membaca siswa. Hal ini turut andil memberikan pengaruh menurunnya minat baca pada siswa. Siswa yang terlibat dalam kegiatan membaca nyaring menggunakan aplikasi Lets Read adalah siswa kelas I dan II Sekolah Dasar Semangat Dalam 2 Barito Kuala. Pemilihan subyek pendampingan ini merujuk pada penelitian sebelumnya mengenai kemampuan membaca permulaan. Kemampuan membaca permualaan merupakan kunci bagi keberhasilan pembelajaran di tingkat selanjutnya. Aplikasi Lets Read menjadi solusi untuk mengatasi permasalahan minat baca siswa yang rendah. Tujuan pengabdian ini yaitu meningkatkan minat baca siswa dan pengenalan literasi digital bagi anak. Metode yang diterapkan yaitu survey ke sekolah, penentuan subyek pendampingan kegiatan membaca, dan pelaksanaan. Hasil kegiatan adalah meningkatnya minat baca siswa, terutama membaca permulaan bagi siswa kelas rendah. Sehingga proses pembelajaran berjalan efektif dan efisien.Abstract: Reading ability is a skill that cannot be produced instantly. Reading skills need to be familiarized in students' daily lives, especially low-grade students who are still in the early reading stage. The Covid-19 pandemic has affected students' reading habits. This also contributes to the decreased interest in reading in students. Students who are involved in reading aloud using the Lets Read application are students in grades I and II of the Spirit Elementary School 2 Barito Kuala. The choice of the subject of this mentoring refers to previous research on early reading skills. The ability to read the beginning is the key to successful learning at the next level. The Lets Read application is a solution to overcome the problem of low student interest in reading. The purpose of this service is to increase students' reading interest and the introduction of digital literacy for children. The methods applied are surveys to schools, determination of mentoring for reading activities, and implementation. The result of the activity is an increase in students' interest in reading, especially early reading for lower grade students. So that the learning process runs effectively and efficiently.